SOME PRELIMINARY CALCULATED RESULTS OF THE POSSIBILITY OF THERMAL TRANSMISSION FROM COOLING WATER SOURCES OF NUCLEAR POWER PLANTS IN NINH THUAN COASTAL AREAS - Bac, Phan Thanh; Long, Bui Hong; The, Ho Van (Vietnam Journal of Marine Science and Technology, 2016)
This paper presents the results of the initial calculation of ability to spread heat from the cooling water of nuclear power plants in Ninh Thuan coastal waters. Model MIKE 21 is used to calculate the thermal transmission with the assumed volume of cooling water for the units of 2 nuclear power plants I and II. Based on various data sources (domestic and foreign), historical data, local survey in 2014, the conditions for calculating and calibrating the model were made. The calculations were carried out for 2 seasons, the dry season and the rainy season, in the research area, the results show that: The cooling water discharge from the two nuclear power plants has ability to influence the sea temperature of surrounding areas; In dry season the temperature of waters around the two plants may increase from 0.5 to 2.50C compared to the surrounding waters; In the rainy season, the impact of temperature discharge from nuclear power plants on Phan Rang bay is not much due to by the strong outflow of rainwater discharge from the Cai river; Thermal propagation of seawater in both seasons follows a trend from north to south; The above results are initial calculated results from the projects of Institute of Oceanography during the years from 2013 to 2015; These results can be considered as a scientific basis for management and evaluation to conduct the further research on the impact of the Ninh Thuan nuclear power plants on the coastal ecosystems of the surrounding area in the further.